Exploring the factors that influence engagement with and experiences of integrated care for adults at risk of cardiovascular disease and mild-to-moderate mental health concerns in the UK (OptICS): a systematic review protocol : protocol - McKinlay, Alison R.; Howlett, Neil; Antonopoulou, Vivi; Lorencatto, Fabiana; McGowan, Laura J.; Osborn, David; O’Donnell, Amy; Oliver, Emily J.; Vlaev, Ivo; Sniehotta, Falko F.; Kelly, Michael P.; Michie, Susan; et al. (Systematic Reviews, 2025)
Cardiovascular disease (CVD) is one of the leading causes of premature death globally. CVD is expensive to treat and therefore carries a significant cost for public healthcare systems and the people in them. Those most likely to develop CVD often report co-occurring mental health concerns such as depression and anxiety, in addition to behavioural factors (e.g. physical inactivity) and physical health conditions (e.g. hypertension, high cholesterol, obesity and diabetes). Due to these inter-connecting issues, healthcare provision for CVD patients necessitates a joined-up care pathway providing holistic, person-centred support. Despite the rapid emergence and growth in attempts to deliver such care, evidence concerning how it is experienced and how to promote engagement is fragmented. This review aims to capture the experiences and factors that influence integrated care engagement, reported by adults with CVD risk factors and mild-to-moderate mental health concerns. This systematic review protocol will be reported according to the updated Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA-P) guidelines. Proposed database searches will include Emcare, MEDLINE, PsycINFO (via OVID), CINAHL and preprint databases for grey literature. Articles of interest will include adults’ experiences of and factors that influence engagement with integrated care in the UK, specifically for support with CVD risk and mild-to-moderate mental health concerns. Any study design reporting qualitative primary data will be included (excluding conference abstracts). Data on study population (actors/targets), what they do (behaviours) care setting (context), care format (time) and participant experiences and perspectives will be extracted. Where appropriate, thematic synthesis of extracted data will be coded to the Theoretical Domains Framework (TDF), updated Consolidated Framework for Implementation Research (CFIR) and Action, Actor, Context, Target and Time (AACTT) framework. Findings from this review will provide foundation evidence for a behavioural systems map and recommendations for policymakers, commissioners and those involved or interested in integrated care for people at risk of CVD with mental health concerns. Such evidence can be used to develop future intervention strategies to assist the optimisation of integrated care. Systematic review registration: PROSPERO (CRD42024554282.
Gesehen am 10.11.2025